'True Day Case' Laparoscopic Cholecystectomy in a High-Volume Specialist Unit and Review of Factors Contributing to Unexpected Overnight Stay. (24th July 2018) - Solodkyy, A.; Hakeem, A. R.; Oswald, N.; Di Franco, F.; Gergely, S.; Harris, A. M.
Abstract : Introduction . Laparoscopic cholecystectomy (LC) is the gold standard treatment for gallstones. British Association of Day Case Surgery recommends at least 60% of LCs be performed as day cases. The aim of this study was to assess our rate of true day case LCs and review factors preventing same-day discharge. Methods . We prospectively collected data of all elective LCs performed in a district general hospital over 32 months. Results . 500 patients underwent LC during this period; 438 (88.2%) patients were planned day cases and 59 patients (11.8%) planned overnight stays. Of the planned day cases, 75.8% (n=332) were discharged on the same day and 106 (24.2%) had unexpected overnight stay (UOS). Most patients with BMI >35 and ASA3 planned day case patients were successfully discharged. Drain insertion, longer operations, and late recovery departure were the main reasons for UOS. There were more complications in this group compared to day cases. Conclusions . This unit has a high 'true day case' rate of 75.8%. High BMI and ASA3 should not be absolute contraindications to day case surgery. The majority of unexpected overnight stays are unavoidable but may be reduced by patient selection, stringent preoperative assessment, operation scheduling, and reduction in unnecessary drain insertion.